Antimicrobial efficacy of the combinations of Acacia nilotica, Murraya koenigii (Linn.) Sprengel, Eucalyptus, and Psidium guajava on primary plaque colonizers: An in vitro study - Byalakere Rudraiah Chandra Shekar; Ramesh Nagarajappa; Rupal Singh; S Suma; Rupesh Thakur (Wolters Kluwer Medknow Publications, 2016)
Background: The rise in disease incidence, increased resistance of pathogenic bacteria to currently used antibiotics and chemotherapeutics, opportunistic infections in immunocompromised individuals, and financial considerations in developing countries necessitates alternate preventive and treatment strategies for oral diseases. Objective: The objective of the study is to assess the antimicrobial efficacy of triple and quadruple combinations of Acacia nilotica (AN), Murraya koenigii (Linn.) (MKL) Sprengel, Eucalyptus (Euca), and Psidium guajava (PS) on primary plaque colonizers. Materials and Methods: The phytochemicals in four plants were extracted using Soxhlet apparatus. The dried extracts were diluted with dimethyl sulfoxide (DMSO) to prepare stock solutions (100 mg/ml) of each plant. The triple and quadruple combinations were prepared after mixing equal quantities of stock solutions from each plant extracts. The antimicrobial efficacy testing was done on Streptococcus mutans, Streptococcus sanguis, and Streptococcus salivarius using agar well diffusion method. Chlorhexidine of 0.2% composition and DMSO were used as positive and negative controls, respectively. The mean diameter of inhibition zone between different categories was compared using one-way analysis of variance. Results: The combination of AN + MKL Sprengel + Euca + PS produced the highest mean diameter of inhibition zone (23.5 ± 2.17 mm) against S. mutans. The combination of AN + MKL Sprengel + Euca produced the maximum antimicrobial efficacy against S. sanguis (19.83 ± 1.33). Conclusion: All the triple and quadruple combinations of the plant extracts offered antimicrobial benefits either superior or comparable to 0.2% chlorhexidine against S. mutans, S. sanguis, and S. salivarius.